DINAMIKA POLITIK HUKUM DALAM POSITIVISASI HUKUM PERDATA ISLAM DI INDONESIA - Sabubu, Theo Alif Wahyu (HUNILA : Jurnal Ilmu Hukum dan Integrasi Peradilan, 2025)
This article aims to analyze the political-legal dynamics in the process of the positivization of Islamic civil law in Indonesia from the colonial period, independence, the Old Order, the New Order, up to the reform era. The focus of the study is directed toward explaining how political configurations, socio-religious forces, and the state’s ideological orientation influence the level of acceptance, forms of regulation, and scope of application of Islamic law within the national legal system. This research employs a normative-juridical method with a historical approach, involving analysis of legislation, doctrinal sources, and the political-legal dynamics underlying the legislative process. The findings show that the positivization of Islamic civil law has taken place gradually through compromises between nationalist-secular and nationalist-Islamic political forces, with Pancasila serving as the philosophical foundation for harmonizing sharia norms with national law. The conclusion emphasizes that the success of the positivization of Islamic law is strongly influenced by political configurations, the consolidation of the Muslim community, and the ability to formulate sharia norms that are contextual, moderate, and aligned with the principles of the Pancasila-based rule of law